Investigating Online Learning Implementation in Indonesia; Challenges and Possible Solution - Muslem Daud; Bor-Chen Kuo; T. Abdurahman; Mariati MR; Yusrizal Yusrizal; Sariakin Sariakin (Universitas Serambi Mekkah, 2022)
Online learning has been become a trend as media in teaching and learning. This digital learning media used in various levels of education, from basic to tertiary levels. This fact is not only because of Covid-19 has been taking place for some years ago, but it has been becoming innevatable teaching and learning modes nowadays. Nevetheless, for some developing countries, including Indonesia, online learning implementation still challenges. This reserach investigated teachers readiness to use those technologies devices to run classroom by using online learning. Research sample of primary school teachers were 55 Indonesian teachers.The data were analyzed using the simple percentage method. The results shows there are teachers face challeges in using online learing. I related to teachers competencies and limited online infrastructure available. These two situation need to be paid attention by schools as well the government particularly telecommunication department. Training and mentoring as well as expanded access to fast internet connection required for online teaching would be the suggestion of the study. Keywords: Online Teaching, Online Learning, Technology Education